New ideas, Management, Plan, Money, and Teamwork for New Business Effectiveness: Digital Transformation as Moderator. - Markhumah, Umatun; Intan Penatari, Resi; Septiana, Aulia (Journal Economic Business Innovation, 2025)
Purpose: This study looks at how five important entrepreneurial factors affect startup performance in a changing business environment. These factors are innovation capability, entrepreneurial leadership, strategic agility, access to funding, and collaborative networks. Digital transformation is a factor that can change how these factors affect performance. Method: We employed a quantitative research design to collect primary data through structured questionnaires that we distributed to 250 startup founders and managers. The relationships between the variables were analyzed using structural equation modeling (SEM), and the moderating role of digital transformation was tested. Findings: It is indicated by the results that startup performance is significantly and positively influenced by all five entrepreneurial factors. Digital transformation has a significant impact on these relationships, enhancing their effect on performance outcomes. Novelty: This research contributes novel insights. It does so by integrating digital transformation as a moderator. It also illuminates how digital capabilities interact with traditional entrepreneurial drivers. This interaction improves startup success in rapidly evolving markets. Implications: Entrepreneurs, investors, and policymakers can use the findings to guide their actions. The findings suggest that these groups prioritize digital transformation initiatives alongside essential entrepreneurial competencies. These initiatives will foster startup growth, resilience, and competitive advantage.